Effectiveness of Universal Concept of Mental Arithmetic System (UCMAS) In The Developing Of Visual Thinking Among Fourth Grade Students (Quasi- Experimental Study In Private Schools At Lattakia) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This search aimed to investigate the Effectiveness of Universal Concept of Mental Arithmetic System (UCMAS) In The Developing Of Visual Thinking including the skills of (recognizing and describing the geometric shape, shape analyzing, realization symmetry between the shapes, realization difference between the shapes) Among Fourth Grade Students In Private Schools At Lattakia. The researcher had used two tools; Universal Concept of Mental Arithmetic System program and visual thinking test including the skills of (recognizing and describing the geometric shape, shape analyzing, realization symmetry between the shapes, realization difference between the shapes).The research had applied for sample which consists of 30 students were selected at simple random way from Private Al Amal School. The sample had divided equally into control and experimental groups. The results of the research were as following: - There are statistical significant different at 0.01 level between the control and experimental students' mean grades in the post- visual thinking test . - There are statistical significant different at 0.01 level between the experimental students' mean grades in pre and post visual thinking test.